Efectos comunicativos del programa el combo amarillo y su incidencia en los jóvenes entre 13-14 años de edad en la unidad educativa Santiago de las Praderas - Desimavilla Espinoza, Erika Liliana (2016)
The purpose of this research was to diagnose the communicative effects of the television program "The Yellow Combo" in students. The research was conducted through surveys that youth were applied whose age ranges from 13 to 14 years old, studying in the Educational Unit "Santiago Prairie" located in the Ximena Parish in Prairie 1 Citadel City Guayaquil in the Guayas Province, 2015-2016 school year. The rationales that determine this research work are psychological, sociological and legal type. We used a documentary and field research because the researcher-reality to obtain the data insitu for information on how to proceed youth surveyed before watching a television comedy program interaction……